2021
DOI: 10.7554/elife.71572
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary footprints of a cold relic in a rapidly warming world

Abstract: With accelerating global warming, understanding the evolutionary dynamics of plant adaptation to environmental change is increasingly urgent. Here we reveal the enigmatic history of the genus Cochlearia (Brassicaceae), a Pleistocene relic that originated from a drought-adapted Mediterranean sister genus during the Miocene. Cochlearia rapidly diversified and adapted to circum-Arctic regions and other cold-characterized habitat types during the Pleistocene. This sudden change in ecological preferences was accomp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 143 publications
(293 reference statements)
2
28
0
Order By: Relevance
“…danica were considered as a separate cluster 4, which shows closest affinities with Mediterranean Ionopsidium representing cluster 5 also defined exclusively by monocarpic taxa. These results are consistent with the findings of Wolf et al (2021), who identified the same groups based on nine of the 19 bioclimatic variables. These results show that Cochlearia and Ionopsidium accessions are exposed to varying environmental conditions, which is expected considering their geographically distant distribution.Ionopsidium accessions can be aggregated into a single group, suggesting that they inhabit regions with similar precipitation rates and temperatures.…”
Section: Bioclimatic Niche Characteristics Of Analyzed Cochlearia And...supporting
confidence: 91%
See 4 more Smart Citations
“…danica were considered as a separate cluster 4, which shows closest affinities with Mediterranean Ionopsidium representing cluster 5 also defined exclusively by monocarpic taxa. These results are consistent with the findings of Wolf et al (2021), who identified the same groups based on nine of the 19 bioclimatic variables. These results show that Cochlearia and Ionopsidium accessions are exposed to varying environmental conditions, which is expected considering their geographically distant distribution.Ionopsidium accessions can be aggregated into a single group, suggesting that they inhabit regions with similar precipitation rates and temperatures.…”
Section: Bioclimatic Niche Characteristics Of Analyzed Cochlearia And...supporting
confidence: 91%
“…Information on chromosome number and ploidy level is provided in Suppl. Material Table 1 (Koch et al, 1996;Koch et al, 1998;Koch et al, 1999;Koch, 2002;Koch et al, 2003;Koch & Bernhardt, 2004;Cieslak et al, 2007;Koch, 2012;Wolf et al, 2021).…”
Section: Analysis Of Electrolytic Leakage Datamentioning
confidence: 99%
See 3 more Smart Citations